Analisis Pola Konsumsi Pangan Rumah Tangga Agroindustri Tahu di Desa Petung Kecamatan Bangsalsari Kabupaten Jember - Yasin, Moh. (Program Studi Agribisnis, 2022)
A person's food consumption pattern can be influenced by a person's income. The quality of the population's food consumption can be reflected in the amount of the expected food pattern score (PPH). One of the business sectors that often experience fluctuations in income is tofu agroindustry. This study was conducted to determine the socioeconomic characteristics of the household and to determine the household food consumption pattern of Tofu Agroindustry in Petung Village, Bangsalsari District, Jember Regency. The sampling method used the Slovin method and the sampling method used the accidental method. This study uses primary data obtained using the interview method and analyzed descriptively. PPH calculation is carried out according to the PPH scoring formula and the National PPH Composition table. The results showed that (1) the socio-economic characteristics of tofu agroindustry households included: the average household income of tofu agroindustry was Rp. 60,129.00 in the low category because it was still below the minimum wage, the average number of family members was 5 people, the average age the average housewife is 45 years old, and the length of education is 9 years; (2) the PPH score is 82.66, which means that the household food consumption pattern of tofu agroindustry in Petung Village, Bangsalsari District, Jember Regency is still not diverse and balanced.